FENOMENA PERCERAIAN DI KALANGAN GENERASI MUDA MUSLIM: PERSPEKTIF HUKUM KELUARGA ISLAM - Abdurahman, Abdurahman; Lutfi, Chairul; Ahmad, Lia Fauziyyah; Nurlia, Nurlia (Hikmah: Journal of Islamic Studies, 2025)
AbstractThe incidence of divorce among young Muslim couples in Indonesia has seen a significant rise in recent years, influenced by various factors such as economic instability, shifts in social values, and the impact of social media. This study aims to analyze the underlying causes of divorce among young Muslims and to examine the role of Islamic family law as a preventive measure. Employing a qualitative approach with a juridical-sociological design, the research utilizes in-depth interviews and document analysis involving divorced young couples, religious courts, and religious institutions. The findings reveal that economic pressures, changes in social values, emotional instability, and the influence of social media significantly contribute to the increasing divorce rates. While Islamic family law, emphasizing mediation and reconciliation, serves as a preventive tool, challenges arise from the limited understanding of Islamic legal principles among young couples. Consequently, this study recommends the enhancement of premarital education based on Islamic principles and the strengthening of mediation efforts within religious courts to reduce divorce rates. The research is expected to contribute to the development of more effective policies aimed at strengthening the institution of marriage among young Muslim couples.AbstrakFenomena perceraian di kalangan generasi muda Muslim di Indonesia menunjukkan peningkatan yang signifikan dalam beberapa tahun terakhir, dipengaruhi oleh faktor ekonomi, sosial, budaya, dan pengaruh media sosial. Penelitian ini bertujuan untuk menganalisis faktor-faktor penyebab perceraian dan memahami peran hukum keluarga Islam sebagai upaya pencegahan. Penelitian ini menggunakan pendekatan kualitatif dengan desain yuridis-sosiologis, melalui wawancara mendalam dan studi dokumentasi dengan pasangan muda yang bercerai, pengadilan agama, dan lembaga keagamaan. Hasil penelitian menunjukkan bahwa faktor ekonomi, perubahan nilai sosial, ketidakstabilan emosional, dan media sosial berkontribusi besar terhadap meningkatnya angka perceraian. Meskipun hukum keluarga Islam yang menekankan pada mediasi dan rekonsiliasi berfungsi sebagai upaya pencegahan, tantangan besar muncul dari kurangnya pemahaman pasangan muda terhadap hukum Islam. Oleh karena itu, penelitian ini merekomendasikan peningkatan pendidikan pranikah berbasis syariah dan penguatan mediasi di pengadilan agama sebagai langkah strategis untuk mengurangi angka perceraian. Penelitian ini diharapkan memberikan kontribusi dalam pengembangan kebijakan yang lebih efektif untuk memperkuat institusi perkawinan di kalangan generasi muda Muslim.